Study of Gravitational Waves GW150914 and GW170104 as a Black Hole Merger - Mathew, G.; Louie Frobel, P. G. (Astrophysical bulletin, 2024)
Gravitational waves are ‘‘ripples’’ in space-time caused by some of the most violent and energetic processes in the Universe. A study of gravitational waves GW150914 and GW170104 was carried out using strain data from LIGO (Laser Interferometer Gravitational Wave Observatory). The analysis presented is consistent with the published results on the subject. It was found that both systems produced gravitational waves from a pair of inspiraling black holes that approached very closely before merging. Different properties of the systems like chirp mass, compactness ratio, luminosity distance, eccentricity, redshift, and spin parameter were studied and the nature of the system was identified from the results.